Thoracolumbar Spine Surgery: Peri-operative Nursing Care Needs and Quality of Life - Geeta Thapar; Manju Dhandapani; Sivashanmugam Dhandapani; Navneet Singla (International Journal of Orthopedic Nursing and Practices, 2023)
Aim and Objective: To explore the nursing care needs of the patients after thoracolumbar spine surgery during preoperative, post-operative, home care and to assess the quality of life. Design: An exploratory study. Methods: The study was conducted among 50 patients who had undergone thoracolumbar spine surgery in neurosurgery units of tertiary care hospital from July 2018 to September 2020. The nursing needs were assessed by interviewing participants telephonically using an interview schedule to assess physical, psychological, functional, and other problems and WHOQOL-BREF to assess the quality of life. The data was coded and analyzed using SPSS version 20. Results: The physical problems were pain, numbness, and weakness of limbs. The psychological problems were worry, sleeplessness, dysthymia, and anger. The functional problems were difficulty in toileting and transferring. Patients also reported lack of understanding of the surgical procedure and its outcomes and difficulty in understanding specific instructions. Pain was reduced from 98% to 90% after surgery but was consistently there during the peri-operative period. There was a reduction in numbness after surgery (98% to 68%). The quality of life in psychological and physical domain is more affected as compared to environmental and social domain. More than half of the patients reported quality of life as “neither poor nor good” and 14% reported dissatisfaction with their health. Conclusion: Patients who had undergone thoracolumbar spine surgery experienced various problems during their peri-operative period. Besides physical problems, patients also reported psychological problems and knowledge deficit regarding home care. Physical and psychological domains of quality of life was more affected as compared to environmental and social domains. Impact: There is a need to develop nursing guidelines and nurse-led counselling is necessary to address the many physical and psychological concerns that patients confront throughout their peri-operative time.
Keywords: Thoracolumbar spine surgery; WHOQOL-BREF; nurse-led counselling; nursing care needs; peri-operative period